PEMASARAN KERIPIK PISANG KHARISMA PADA MASA PANDEMIK DI BANDAR LAMPUNG - Endang Kasihati; Eka Kasymir; Yaktiworo Indriani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
This study aimed to analyze the strengths and weaknesses of banana chips marketing in the pandemics period at Kharisma banana chips agroindustry in Bandar Lampung City. This research involved 5 respondents, namely 1 owner, 2 employees, and 2 consumers.  The research data was collected in January 2022 and analyzed qualitatively and quantitatively. Qualitative analysis was conducted based on the field observations and direct interviews with business owners, production employees, sales employees, and consumers. Quantitative analysis was conducted by calculating the EFE, IFE, and IE matrices. The results showed that the internal factors in the marketing of the agroindustry of Kharisma banana chips were product, price, promotion, human resources, physical evidence, and process while external factors were competitors, consumers, technology, suppliers, and the government. The condition that occurred in the marketing of the Agroindustry during the pandemic was that the turnover was decreasing because the number of consumers was reducing due to the pandemic.  Keywords:   Agroindustry, Banana, Marketing, Pandemic